KOMITMEN ZERO WASTE INDUSTRY PT. MORINAGA DALAM MENGOLAH LIMBAH SLUDGE SUSU MENJADI PUPUK PADAT - Chairumin Alfin; Bayu Buwana; Heru Setiyo Cahyono (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
This Community Service (PkM) activity aims to implement thermal drying technology to assist PT. Morinaga in processing dairy sludge waste into high-value solid fertilizer, as a tangible manifestation of the Zero Waste Industry commitment. The main problem identified at the company's Wastewater Treatment Plant (WWTP) is the accumulation of biological sludge waste with an initial moisture content reaching 85%. This high moisture content triggers a rapid decomposition process and produces extreme odor pollution in less than 24 hours, risking operational comfort and environmental safety. The problem-solving method applied by the service team is Rotary Drum Dryer (RDD) technological engineering, accompanied by technical training for 15 internal staff and technicians of PT. Morinaga. Scientific findings show that RDD implementation can evaporate water instantly, reducing the moisture content to 14%, and shrinking the waste mass from 12 tons to only 1.8 tons per day. The resulting solid fertilizer is proven to meet the SNI 19-7030-2004 agronomic quality standards. The conclusion of this activity proves that comprehensive thermal technology intervention successfully breaks the chain of decomposition, eliminates odor pollution in the factory area, reduces waste management logistics costs by up to 80%, and creates material circulation that supports the company's Corporate Social Responsibility (CSR) programs. The results of this community service set a new precedent and operational standard for PT. Morinaga in sustainable industrial waste governance.